2011
DOI: 10.1128/aac.00168-11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vancomycin Trough Concentrations and Nephrotoxicity: a Prospective Multicenter Trial

Abstract: Several single-center studies have suggested that higher doses of vancomycin, aimed at producing trough concentrations of >15 mg/liter, are associated with increased risk of nephrotoxicity. We prospectively assessed the relative incidence of nephrotoxicity in relation to trough concentration in patients with documented methicillin-resistant Staphylococcus aureus (MRSA) infections at seven hospitals throughout South Carolina. Adult patients receiving vancomycin for at least 72 h with at least one vancomycin tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
193
4
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(213 citation statements)
references
References 35 publications
11
193
4
5
Order By: Relevance
“…2). In addition, troughs of Ն15 mg/liter remained significantly associated with nephrotoxicity when articles (8,13,21,22,30,36,43) in which authors declared potential conflicts of interests with pharmaceutical companies were excluded (OR, 2.84; 95% CI, 1.65 to 4.87; P Ͻ 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). In addition, troughs of Ն15 mg/liter remained significantly associated with nephrotoxicity when articles (8,13,21,22,30,36,43) in which authors declared potential conflicts of interests with pharmaceutical companies were excluded (OR, 2.84; 95% CI, 1.65 to 4.87; P Ͻ 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of nephrotoxicity varied between studies from 5% to 43%. On average, nephrotoxicity occurred between 4.3 and 17 days after initiation of vancomycin therapy (13,21,22,30,32,36,38,39,43,51). The definition of nephrotoxicity was identical (increase in serum creatinine [S CR ] of 0.5 mg/dl, equivalent to 44.2 mol/liter or 50% from baseline on 2 consecutive measurements) in all but three studies ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter prospective clinical trial, including 288 adult patients (70), and a recent meta-analysis (71) have reaffirmed the high probability of nephrotoxicity with vancomycin trough levels of Ͼ15 mg/liter. This threshold is not uniform in all studies, and other authors have found that recommended dosages of vancomycin with target troughs of 15 to 20 mg/liter are not an independent risk factor for nephrotoxicity (72).…”
Section: Vancomycin Toxicitymentioning
confidence: 99%
“…In recent years, vancomycin dosing has escalated, driven by concerns of increasing treatment failure, thought to be the result of increasing vancomycin MICs (MIC creep) among S. aureus isolates (4)(5)(6). Consequently, this strategy may lead to increased rates of nephrotoxicity (7)(8)(9)(10). This risk appears to be highest for patients who are particularly vulnerable to acute kidney injury due to comorbidities such as preexisting renal disease, acute illness, hypoperfusion from sepsis, or concomitant nephrotoxic medication (10,11).…”
mentioning
confidence: 99%